2021
DOI: 10.1186/s13063-021-05403-5
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of equipoise in trials with a surgical and non-surgical comparison: a qualitative synthesis using meta-ethnography

Abstract: Background Randomised controlled trials in surgery can be a challenge to design and conduct, especially when including a non-surgical comparison. As few as half of initiated surgical trials reach their recruitment target, and failure to recruit is cited as the most frequent reason for premature closure of surgical RCTs. The aim of this qualitative evidence synthesis was to identify and synthesise findings from qualitative studies exploring the challenges in the design and conduct of trials dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 101 publications
(289 reference statements)
0
26
0
Order By: Relevance
“…Parents struggled with what they perceived was a severe injury and the stark contrast they faced between surgical and non-surgical treatment. Other studies amongst adults taking part in surgical trials identify participants often struggle to make a decision regarding trial inclusion, which is more marked when the injury is severe or there is a substantial difference between the treatments [ 17 , 18 ]. In this study parents believed that surgery would guarantee that their child’s arm would straighten.…”
Section: Discussionmentioning
confidence: 99%
“…Parents struggled with what they perceived was a severe injury and the stark contrast they faced between surgical and non-surgical treatment. Other studies amongst adults taking part in surgical trials identify participants often struggle to make a decision regarding trial inclusion, which is more marked when the injury is severe or there is a substantial difference between the treatments [ 17 , 18 ]. In this study parents believed that surgery would guarantee that their child’s arm would straighten.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of embracing uncertainty has been widely reported and discussed in the literature. 27 , 28 ‘Equipoise’ is a state of equilibrium, while ‘clinical equipoise’ refers to a state of genuine uncertainty regarding the effectiveness of different interventions. The belief in clinical equipoise has been shown to be key to participants' consent to randomization.…”
Section: Discussionmentioning
confidence: 99%
“…The belief in clinical equipoise has been shown to be key to participants' consent to randomization. 29 A comprehensive review by Davies et al 27 found that the a priori preferences for treatment of both patients and clinicians, as well as the imbalanced presentation of interventions were important themes relating to recruitment problems in clinical trials. While Rooshenas et al 28 investigated how clinicians conveyed equipoise in six clinical trials, finding that while clinicians intended to set their personal biases aside, equipoise was omitted or compromised in 46% of the recorded appointments.…”
Section: Discussionmentioning
confidence: 99%
“…Despite practitioner intentions to set aside personal biases and neutrally convey trial arms, equipoise is commonly omitted or compromised in trial discussions [ 10 ]. Imbalanced presentation of trial arms can influence patient views towards trial arms and willingness to participate in a trial [ 11 ].…”
Section: Introductionmentioning
confidence: 99%